Analysis Of The Implementation Of Zakat And Infaq/Alms Accounting Based On Psak 109 Concerning Zakat And Infaq/Alms Accounting (Study At Baznas Tanggamus Regency) - Hasan, Novanza; Eliza, Any; Suhendar, Suhendar; Nurlaili, Nurlaili; Marjuni, Kamaluddin Nurdin (Al-Kharaj: Journal of Islamic Economic and Business, 2024)
Zakat is part of the pillars of Islam, namely the third pillar of Islam. Zakat is an obligatory and important act of worship. There are many verses in the Qur'an that explain zakat along with other obligatory acts of worship, namely the shahada, prayer, fasting and pilgrimage for those who are able. 109. This research aims to determine the zakat accounting standards at BAZNAS Tanggamus Regency and to understand their suitability for zakat accounting standards based on the Statement of Financial Accounting Standards (PSAK) No. 109 .This research method is a qualitative research method with a comparative descriptive approach. The data collection method used in this research uses observation, interviews and documentation methods. Meanwhile, data analysis uses comparative descriptive.The results of this research can be concluded that BAZNAS Tanggamus Regency has not implemented PSAK No. 109 Concerning Accounting for Zakat, Infaq/Shadaqah. This can be proven by the non-compliance of the 4 indicators listed in PSAK No. 109, namely recognition, measurement after recognition, presentation and disclosure. This is motivated by the recent educational background of employees and staff who work at BAZNAS Tanggamus Regency. The average educational background of employees and staff is a religious graduate, and the lack of finance staff is the reason why PSAK No. 1 has not been implemented. 109, as well as minimal government supervision and outreach regarding PSAK No. 109 Concerning Zakat, Infaq/Shadaqah Accounting for BAZNAS Tanggamus Regency